Early Life Allergen and Air Pollutant Exposures Alter Longitudinal Blood Immune Profiles in Infant Rhesus Monkeys - Crowley, Candace M. (Toxicol Appl Pharmacol, 2017)
Early life is a critical period for the progressive establishment of immunity in response to environmental stimuli; the impact of airborne challenges on this process is not well defined. In a longitudinal fashion, we determined the effect of episodic house dust mite (HDM) aerosol and ozone inhalation, both separately and combined, on peripheral blood immune cell phenotypes and cytokine expression from 4-25 weeks of age in an infant rhesus monkey model of childhood development. Immune profiles in peripheral blood were compared with lung lavage at 25 weeks of age. Independent of exposure, peripheral blood cell counts fluctuated with chronologic age of animals, while IFNγ and IL-4 mRNA levels increased over time in a linear fashion. At 12 weeks of age, total WBC, lymphocyte numbers, FoxP3 mRNA and IL-12 mRNA were dramatically reduced relative to earlier time points, but increased to a steady state with age. Exposure effects were observed for monocyte numbers, as well as CCR3, FoxP3, and IL-12 mRNA levels in peripheral blood. Significant differences in cell surface marker and cytokine expression were detected following in vitro HDM or PMA/ionomycin stimulation of PBMC isolated from animals exposed to either HDM or ozone. Lavage revealed a mixed immune phenotype of FoxP3, IFNγ and eosinophilia in association with combined HDM plus ozone exposure, which was not observed in blood. Collectively, our findings show that airborne challenges during postnatal development elicit measureable cell and cytokine changes in peripheral blood over time, but exposure-induced immune profiles are not mirrored in the lung.